(d+3)(9d-2)=0

Simple and best practice solution for (d+3)(9d-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (d+3)(9d-2)=0 equation:


Simplifying
(d + 3)(9d + -2) = 0

Reorder the terms:
(3 + d)(9d + -2) = 0

Reorder the terms:
(3 + d)(-2 + 9d) = 0

Multiply (3 + d) * (-2 + 9d)
(3(-2 + 9d) + d(-2 + 9d)) = 0
((-2 * 3 + 9d * 3) + d(-2 + 9d)) = 0
((-6 + 27d) + d(-2 + 9d)) = 0
(-6 + 27d + (-2 * d + 9d * d)) = 0
(-6 + 27d + (-2d + 9d2)) = 0

Combine like terms: 27d + -2d = 25d
(-6 + 25d + 9d2) = 0

Solving
-6 + 25d + 9d2 = 0

Solving for variable 'd'.

Factor a trinomial.
(-3 + -1d)(2 + -9d) = 0

Subproblem 1

Set the factor '(-3 + -1d)' equal to zero and attempt to solve: Simplifying -3 + -1d = 0 Solving -3 + -1d = 0 Move all terms containing d to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1d = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1d = 0 + 3 -1d = 0 + 3 Combine like terms: 0 + 3 = 3 -1d = 3 Divide each side by '-1'. d = -3 Simplifying d = -3

Subproblem 2

Set the factor '(2 + -9d)' equal to zero and attempt to solve: Simplifying 2 + -9d = 0 Solving 2 + -9d = 0 Move all terms containing d to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -9d = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -9d = 0 + -2 -9d = 0 + -2 Combine like terms: 0 + -2 = -2 -9d = -2 Divide each side by '-9'. d = 0.2222222222 Simplifying d = 0.2222222222

Solution

d = {-3, 0.2222222222}

See similar equations:

| 9x+29=4 | | 11/x=x/11 | | -5(t-2)-7= | | 42=2y-10 | | 10*1/3= | | 8y^2+8y+7=0 | | 9a-4(2a+5)=a-20 | | 8=x+29 | | -5=(2x+1) | | 5x+3=13+4x | | 1/10*2= | | Y=-100+4x^2 | | (x+20)(x)=4800 | | 3v(2v+1)=0 | | 4x^2-20x=-21 | | 8*1/4= | | log(2x-1)=0 | | 1/12*4= | | 1/12*6= | | 66=92/11(88)+b | | 19x-61+3x+1=180 | | 10*1/5= | | (6y-6)+4y+24=81 | | 1/3*3= | | 7x4/11 | | 42=-2(n+6)+m | | 5v+3v=16 | | v=(5X-4)(X+4)(2X-1) | | 4.8+x-5=3.6 | | (2n+7)(6n+7)=0 | | 7/12-4/9= | | (-3x)-9=-27 |

Equations solver categories